Von Neumann stability analysis of the FDTD method applied to non‐magnetised plasma antennas. Issue 6 (12th March 2018) - Ghaderi, Mohammadreza; Moradi, Gholamreza
Abstract : The finite difference time domain (FDTD) analysis of plasma antennas, according to the fluid modelling of plasma has matured recently. By coupling other equations such as fluid or Boltzmann momentum relation to Maxwell's equation set, the famous Courant‐Fredrichs‐Lewy stability limit cannot guarantee the convergence of solutions. In plasma cases, explicitly coupling Maxwell's equations with the constitutive equation cause the stability condition to depend on the plasma parameters ( ω p, υ c ) in addition to mesh size, and the denser the plasma is, the less stable solutions are. Here, a well‐founded proof to a modified stability condition is presented using linear algebra for both collision‐less and collisional non‐magnetised plasma. Furthermore, the derived values are validated numerically.